2020
DOI: 10.1016/j.brs.2020.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Task-dependent effects of intracranial hippocampal stimulation on human memory and hippocampal theta power

Abstract: Background: Despite its potential to revolutionize the treatment of memory dysfunction, the efficacy of direct electrical hippocampal stimulation for memory performance has not yet been well characterized. One of the main challenges to cross-study comparison in this area of research is the diversity of the cognitive tasks used to measure memory performance. Objective: We hypothesized that the tasks that differentially engage the hippocampus may be differentially influenced by hippocampal stimulation and the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 71 publications
2
25
0
Order By: Relevance
“…A focus of many brain stimulation therapies is to recapitulate a target neuronal pattern [21,43,44]. Because we show the stimulation parameters that cause different types electrophysiological signals, our work offers guidelines for clinicians to select stimulation frequencies and amplitudes that recreate particular target patterns.…”
Section: Discussionmentioning
confidence: 99%
“…A focus of many brain stimulation therapies is to recapitulate a target neuronal pattern [21,43,44]. Because we show the stimulation parameters that cause different types electrophysiological signals, our work offers guidelines for clinicians to select stimulation frequencies and amplitudes that recreate particular target patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is compelling evidence linking theta oscillations to hippocampal encoding and AM (e.g. [23][24][25][26]. Following this rationale, it was recently demonstrated that high definition theta band transcranial alternating current stimulation (tACS) improves AM performance 27 .…”
mentioning
confidence: 99%
“…The researchers observed an increase in theta activity during memory study and a decrease in the efficiency of the theta wave after memory tasks [9]. As a result of intracranial EEG recording from the hippocampus of 10 epilepsy patients, two different verbal memory tasks were performed, and it was reported to be proportional to theta strength that increased with memory performance by hippocampal stimulation [15]. İshii et al indicated that theta rhythms increased during focused attention on mental computation [10].…”
Section: Discussionmentioning
confidence: 99%